1993
DOI: 10.1007/bf01280841
|View full text |Cite
|
Sign up to set email alerts
|

Energy inversion of thef 7/2 andh 9/2 neutrons in yrast states of154Yb

Abstract: The N=84 nucleus 154yb was investigated through the l~ reaction. We found the 16 + yrast level in this nucleus to be formed by the (~h2w2 xJfT/2hg/2) configuration, in contrast to the 9 " 2 2 + 9lower-Z lsotones where (Xhlv2~f 7/2)16 is the yrast state. Manybody shell model calculations with empirical two-body interactions support our conclusion. PACS: 21.60. Cs; 23.20. Lv;27.70.+q The lowering of the vh~/2 single particle state is a characteristic structure feature in the spherical nuclei above 14~Gd where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 5 publications
1
6
0
Order By: Relevance
“…Long-lived 8 + states have been observed in other nuclei in the region. For example, in the case of 152 Er 84 , a half-life of 1.8 ns [22] has been reported for the 8 + state while in 154 Yb 84 T 1/2 (8 + ) = 28 ns [23]. In both cases, the excitation energy of the yrast I π = 8 + state is lowered, relative to its position in the heavier isotopic neighbor, while the energy of the yrast I π = 6 + state continues to increase with decreasing neutron number.…”
Section: Discussionmentioning
confidence: 99%
“…Long-lived 8 + states have been observed in other nuclei in the region. For example, in the case of 152 Er 84 , a half-life of 1.8 ns [22] has been reported for the 8 + state while in 154 Yb 84 T 1/2 (8 + ) = 28 ns [23]. In both cases, the excitation energy of the yrast I π = 8 + state is lowered, relative to its position in the heavier isotopic neighbor, while the energy of the yrast I π = 6 + state continues to increase with decreasing neutron number.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of isotones in this region have revealed that as the occupancy of the πh 11/2 orbital increases with increasing Z, states involving configurations with neutrons in the h 9/2 orbital are lowered in energy relative to those with neutrons in the f 7/2 orbital [1][2][3][4]. This observation has been attributed to an increasing attraction between h 11/2 protons and h 9/2 neutrons as the occu- * Present address: Department of Physics, University of Surrey, Guildford GU2 7XH, United Kingdom † Present address: Department of Physics, University of Guelph, Guelph, Ontario, N1G 2W1 Canada pancy of the h 11/2 proton orbital increases.…”
Section: Introductionmentioning
confidence: 99%
“…The calculations were performed in the model space ν(h 9/2 , f 7/2 , i 13/2 ) and two-body interactions were taken into account. The single particle energies and the two-body interactions were extracted from the neighboring nuclei 154 Yb [5] …”
Section: Discussionmentioning
confidence: 99%
“…For the eveneven Yb isotopes, the low-lying excitations exhibit a clear structural evolution with neutron number N . For instance, with N decreasing from 88 to 84, 158 Yb shows the behavior of soft rotation [1]; 156 Yb undergoes an evolution from a quasivibrational to quasirotational structure with increasing spin [2,3]; and 154 Yb is interpreted in terms of the quasiparticle coupling [4,5]. For the odd-A Yb isotopes in this transitional region, collective structures built on the f 7/2 , h 9/2 , and i 13/2 neutron orbitals have been observed in 157 Yb [6,7] and the coexistence of different nuclear shapes has been revealed.…”
Section: Introductionmentioning
confidence: 99%